Intersecting Identities, Gender and Health: A Mapping of Adolescent Health Challenges in Bangladesh (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
This article discusses the importance of adolescent health and wellbeing for realising the dreams of future Bangladesh. Using data from secondary sources, the paper provides an overview of the challenges faced by adolescents with a focus on gender and intersectionality. Adolescents have unique health needs that are often neglected, and gender norms and values play a significant role in shaping access to resources and opportunities, eventually affecting the physical, mental, and sexual and reproductive health of males and females differently. The contemporary world becomes constrained for girls and they face additional health risks due to child marriage, childbirth, reduced contraception usage, gender-based violence, malnutrition, household and care giving responsibilities. On contrary, the world tends to open up for boys making them vulnerable to health risks like child labour, occupational injuries, physical violence, substance abuse, and suicide. Furthermore, the marginalised groups of adolescents including sexually diverse groups, children of sex workers, street children, orphans, disabled individuals, coastal and indigenous inhabitants face multiple layers of discrimination and health inequalities due to their geographical, socio-economic, gender and sexual identities. All of these diversities need to be taken into account while designing policies for addressing the specific health needs of different groups. Their health needs should be incorporated from a more holistic and broader perspective, using both gender and intersectional lens. This paper emphasises the necessity to include the perspectives and voices of diverse adolescent groups in policymaking to ensure appropriate and effective solutions.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 69(1), 2024, pp. 33-65